¿Seguimos Educando?: the official distance education program during COVID-19 pandemic and its application in a context of educational segregation - Anderete Schwal, Mariano (Universidad Nacional del Litoral, 2021)
This article analyzes the Seguimos Educando program developed by the Argentine Ministry of Education as a proposal for educational continuity during the lockdown caused by the Covid-19 pandemic. We addressed its application according to official regulations and its effects in terms of educational segregation. It is an exploratory and descriptive study using a qualitative method, including interviews with teachers at elementary school in                                                    the city of Bahía Blanca −Buenos Aires, Argentina− who had to implement that educational tool in a context of inequality. The results of this work revealed that the digital divide, inequalities in household incomes, and the different educational strategies adopted by school teachers restrict the program proposed by the national government, uncovering an extension of educational segregation to the virtual environment.